DNA methylation index and methylation profile of invasive ductal breast tumors - Marzese, Diego Matías (2012)
Breast carcinogenesis is a multistep process that involves both genetic and epigenetic alterations. Identification of aberrantly methylated genes in breast tumors and their relation to clinical parameters can contribute to improved diagnostic, prognostic, and therapeutic decision making. Our objective in the present study was to identify the methylation status of 34 cancer-involved genes in invasive ductal carcinomas (IDC). Each of the 70 IDC cases analyzed had a unique methylation profile. The highest methylation frequency was detected in the WT1 (95.7%) and RASSF1 (71.4%) genes. Hierarchical cluster analysis revealed three clusters with different distribution of the prognostic factors tumor grade, lymph node metastasis, and proliferation rate. Methylation of TP73 was associated with high histological grade and high proliferation rate; methylation of RARB was associated with lymph node metastasis. Concurrent methylation of TP73 and RARB was associated with high histological grade, high proliferation rate, increased tumor size, and lymph node metastasis. Patients with more than six methylated genes had higher rates of relapse events and cancer deaths. In multivariate analysis, TP73 methylation and the methylation index were associated with disease outcome. Our results indicate that methylation index and methylation of TP73 and/or RARB are related to unfavorable prognostic factors in patients with IDC. These epigenetic markers should be validated in further studies to improve breast cancer management. © 2012 American Society for Investigative Pathology and the Association for Molecular Pathology.